Juventud y Pandemia Investigaciones, reflexiones y propuestas - Henríquez, Karla (Ariadna Ediciones, 2023)
This book has the participation of prominent academics and managers of public policies on youth from the southern cone of America. It focuses on the Chilean case, but contains contributions on Brazil and Argentina. The text arises from various meetings that took place in 2020, each of the authors presented research and social programs that they developed during the pandemic period, highlighting the advances and possibilities of working with those who lived through the pandemic as young people. The book adds to an extensive list of contributions to the study of youth from the social sciences, in times of the greatest social experiment in recent centuries, whose planetary nature allows us to analyze both the similarities and the differences in three intertwined dimensions: the expansion of the virus and its health effects -the pandemic-, its social effects -the syndemic-, and public policies to address both situations. This entails the study of inequalities -of class, gender, generation and territory- that the coronavirus has revealed, especially generational inequalities, which are the focus of this compilation.